Genocias ir rezistencija Nr. 31(1) - Brukas , Algirdas; Bubnys, Artūras; Zagreckas, Rimantas; Noreika , Dainius; Burinskaitė, Kristina; Ivanauskas , Vilius; Stalmokaitė , Ignė; Juodis, Darius (Genocidas ir rezistencija, 2012)
Pilnas leidinys